2020
DOI: 10.3390/ijms21010370
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of O-acetylated Gangliosides Expressed in Neuroectoderm Derived Cells

Abstract: The expression and biological functions of oncofetal markers GD2 and GD3 were extensively studied in neuroectoderm-derived cancers in order to characterize their potential as therapeutic targets. Using immunological approaches, we previously identified GD3, GD2, and OAcGD2 expression in breast cancer (BC) cell lines. However, antibodies specific for O-acetylated gangliosides are not exempt of limitations, as they only provide information on the expression of a limited set of O-acetylated ganglioside species. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 43 publications
4
26
0
Order By: Relevance
“…MS/MS fragmentation studies revealed that O-acetylation can occur in a cell type dependent manner on both inner and terminal sialic acid residue of b-and c-series of gangliosides. These data highlight the probable existence of different O-acetylation pathways for gangliosides [51].…”
Section: O-acetylation Of Sialic Acid Residuesmentioning
confidence: 59%
See 4 more Smart Citations
“…MS/MS fragmentation studies revealed that O-acetylation can occur in a cell type dependent manner on both inner and terminal sialic acid residue of b-and c-series of gangliosides. These data highlight the probable existence of different O-acetylation pathways for gangliosides [51].…”
Section: O-acetylation Of Sialic Acid Residuesmentioning
confidence: 59%
“…This method avoids the loss of the O-acetyl group and has led to the characterization of OAcGM1, OAcGD3, OAcGD2, OAcGT3 and OAcGT2 in BC, melanoma and neuroblastoma cell lines in a cell type dependent manner, suggesting that O-acetylated ganglioside expression depends mainly on substrate availability and GD3 synthase expression. MS/MS fragmentation of these O-acetylated gangliosides species showed that O-acetylation can occur both on the terminal and on the subterminal sialic acid of the ganglioside carbohydrate moiety [51]. To get further insight into the position of the O-acetyl group on the sialic acid residue, DMB-labeled sialic acid derivatives extracted from gangliosides from BC cells were analyzed by LC-ES-MS. 9-O-acetyl-N-acetyl-neuraminic acid was identified as the main O-acetylated sialic acid species expressed on gangliosides from BC cells [4,51].…”
Section: Analysis Of O-acetylated and Non-o-acetylated Gangliosides Smentioning
confidence: 99%
See 3 more Smart Citations